Overexcitability in Children Aged 8 and 9 in Parents' Perception. Does Sex Matter? - Małgorzata Jabłonowska; Agnieszka Demianowska; Joanna Łukasiewicz-Wieleba; Wiesława Limont (Nicolaus Copernicus University in Toruń, 2022)
Overexcitabilities (OEs) that manifest themselves in intense, emotional, and deep experiencing are part of the developmental potential in Kazimierz Dąbrowski's Theory of Positive Disinte- gration. Most of the studies of OEs are conducted with gifted individuals, using self-evaluation. The present study was carried out among children randomly selected from a general school population, excluding the selective criterion of high abilities. With the use of the Overexcitabil- ity Inventory for Parents (OIP-II), parents' perceptions of their children's profiles of OEs were collected. The OIP-II consists of six scales: psychomotor, sensual, imaginational, intellectual OEs, plus emotional sensitivity and emotional empathy. The participants were 116 parents of children aged 8 (13 girls, 29 boys) and 9 (37 girls, 37 boys) from Poland. The multivariate analysis of variance (MANOVA) showed that girls scored statistically significantly higher than boys on sensual OE and emotional empathy. Older girls obtained higher scores on sensual OE and younger on emotional empathy. No OE profile of boys was found. The novelty in the present study is a random selection of children from a general population for the study as well as the use of the OIP-II. In the discussion, possible explanations and interpretations of the findings are presented, including a suggestion for the direction of further research.